Dating and Sexual Violence Research in the Schools: Balancing Protection of Confidentiality with Supporting the Welfare of Survivors. Issue 3 (18th September 2017) - Sharkey, Jill D.; Reed, Lauren A.; Felix, Erika D.
Highlights: Youth may not report dating or sexual abuse if they have concerns about confidentiality. No procedures exist to support research participants who are adolescent survivors of abuse. We conducted a structured ethical decision‐making process to solve our ethical dilemma. Our novel protocol helps balance participant confidentiality with survivor welfare. Abstract: Rigorous research and program evaluation are needed to understand the experience of dating and sexual violence among youth and the impact of prevention and intervention efforts. Our dilemma in doing this work occurred when youth disclosed dating and sexual violence on a research survey. What responsibility do researchers have to protect survivors' confidentiality as a research participant versus taking steps to ensure the student has the opportunity to access help? In our evaluation of a pilot dating violence prevention program, our protocols employed widely used procedures for providing resources to participants upon their completion of the survey and de‐identifying survey data. Upon reviewing preliminary survey results, we became concerned that these established procedures were not sufficient to support research participants who were adolescent survivors of dating and sexual violence. We followed a structured ethical decision‐making process to examine legal and ethical considerations, consult with colleagues, consider impacts and alternative solutions, and ultimately find a solution. Through this process, we developed procedures that balance participant confidentiality and the desire to support the welfare of survivors, which other researchers may want to employ when conducting youth sexual and dating violence research in school and community settings.